2006
DOI: 10.1002/ajp.20312
|View full text |Cite
|
Sign up to set email alerts
|

Modeling dichromatic and trichromatic sensitivity to the color properties of fruits eaten by squirrel monkeys (Saimiri sciureus)

Abstract: Most platyrrhines have a visual polymorphism that is characterized by the presence of multiple alleles of the M/LWS gene on the X chromosome. This polymorphism is probably maintained by selection. There are two possible mechanisms by which this can be explained: First, heterozygous females may have perceptual advantages over dichromats, such that trichromacy would be favored via the existence of different visual pigments. This is known as selection by heterosis. Second, dichromacy may be advantageous in some s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…These results accord well with reflectance and modeling studies investigating the detectability of naturally occurring food items to dichromatic and trichromatic primates (de Araujo et al 2006;Hiramatsu et al 2008;Lucas et al 2003;Regan et al 2001;Riba-Hernandez et al 2004;Snodderly 1979;Stoner et al 2005;Sumner and Mollon 2000a), most of which report that trichromats may be better able to detect many, if not most, ingested fruits and leaves, or exploited fruit and leaf species, against a mature leaf background. Importantly, however, our results suggest that such observations may lead to overestimates of the number of instances in which trichromacy would provide an advantage over dichromacy to a foraging primate.…”
Section: Yor Patch Detection and Memorysupporting
confidence: 88%
See 2 more Smart Citations
“…These results accord well with reflectance and modeling studies investigating the detectability of naturally occurring food items to dichromatic and trichromatic primates (de Araujo et al 2006;Hiramatsu et al 2008;Lucas et al 2003;Regan et al 2001;Riba-Hernandez et al 2004;Snodderly 1979;Stoner et al 2005;Sumner and Mollon 2000a), most of which report that trichromats may be better able to detect many, if not most, ingested fruits and leaves, or exploited fruit and leaf species, against a mature leaf background. Importantly, however, our results suggest that such observations may lead to overestimates of the number of instances in which trichromacy would provide an advantage over dichromacy to a foraging primate.…”
Section: Yor Patch Detection and Memorysupporting
confidence: 88%
“…Several modeling studies have suggested that the trichromatic vision of both catarrhines and heterozygous platyrrhines is superior to that of dichromats for detecting both fruits (de Araujo et al 2006;Osorio et al 2004;Regan et al 2001;Riba-Hernandez et al 2004;Stoner et al 2005;Sumner and Mollon 2000a) and young leaves Lucas et al 2003;Sumner and Mollon 2000a) against a background of mature green leaves. In accord with these predictions, in a study of captive marmosets (Callithrix), designed to mimic natural detection tasks at maximum distances of 6 m, Caine and Mundy (2000) found a modest trichromatic advantage over dichromats in distinguishing orange targets against a green/brown background.…”
Section: Selective Advantage Of Trichromacymentioning
confidence: 98%
See 1 more Smart Citation
“…One somewhat interesting leaf adaptation found in Cerrado species that certainly affects background spectra is the presence of hair, especially at lower leaf surfaces, that provide a pale aspect to certain leaves. Similarly from what is usually shown for rainforest species (Sumner and Mollon, 2000b;Regan et al, 2001;Osorio et al, 2004;De Araújo et al, 2006), the upper leaf surfaces from Cerrado trees appear darker and greener than lower leaf surfaces. According to our results, however, subtle differences in background spectra only seem to minimally interfere in target detection by dichromats and trichromats.…”
Section: Background Gradient and Fruit Detectionmentioning
confidence: 51%
“…Recent investigations (Sumner and Mollon, 2000a;Regan et al, 2001;Osorio et al, 2004;Riba-Hernandez et al, 2004;Stoner et al, 2005;De Araújo et al, 2006) seemed to succeed in predicting how different animal phenotypes see their fruit diets against a background of leaves. However, in a natural condition, targets are perceived against a variety of leaf backgrounds and light conditions , which has not yet been extensively considered.…”
mentioning
confidence: 97%